2005
DOI: 10.1002/ange.200501346
|View full text |Cite
|
Sign up to set email alerts
|

Superoxidation of Bisretinoids

Abstract: Eng und persönlich: Eng zusammenstehende Retinoidpolyene, wie sie auf dem rechten Sessel abgebildet sind, reagieren leicht mit Sauerstoff (rot) zu polyoxygenierten Verbindungen. Getrennte Polyene dagegen, wie sie auf dem linken Sofa zu sehen sind, werden nur eingeschränkt oxidiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Because of conjugated double bonds in its hydrophobic arms, A2E exhibits a yellow-orange fluorescence with an emission peak at ∼630 nm (λ max ) (14)(15)(16). Several studies indicate that A2E's λ max changes with the polarity of the medium (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of conjugated double bonds in its hydrophobic arms, A2E exhibits a yellow-orange fluorescence with an emission peak at ∼630 nm (λ max ) (14)(15)(16). Several studies indicate that A2E's λ max changes with the polarity of the medium (17)(18)(19).…”
mentioning
confidence: 99%
“…The absorption spectrum of A2E exhibits two absorbance maxima, at 340 and 440 nm, that correspond to the conjugated double bonds in the short and long arms of the molecule, respectively (14). In aqueous solution, A2E undergoes slow spontaneous oxidation manifested by progressive reduction of its absorbance peaks; upon exposure to blue light (∼430 nm) the oxidative destruction of A2E is much faster (22,23).…”
mentioning
confidence: 99%
“…A2‐E is a singlet oxygen sensitizer, and blue light irradiation in the presence of oxygen for 10 minutes forms a highly apoptotic A2‐E nonaoxirane ( 45 ) 72 . Oxidation products of bisretinoid are proposed to cause cell damage and death 73 . Nakanishi and coworkers showed that photodegradation of A2‐E in vitro and in RPE cells could be prevented by the addition of bilberry or the antioxidant anthocyanins contained therein 74 .…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 15,98,101,103, and 107 led to the formation of bisperoxides. Growing experimental data has been accumulated for singlet oxygen reactions, which give rise to spiro compounds [82,83,[127][128][129][130], or yield bis-or polyperoxides, or polyepoxides [42,58,[114][115][116][117][118][119][120]131].…”
Section: Discussionmentioning
confidence: 99%